Factors affecting biofilm formation as seed transmission mechanism of cowpea bacteria blight induced by Xanthomonas axonopodis pv vignicola (Burkholder) Dye - Simeon, Amodu U.; Shenge, Kenneth C.; Dominic, Akpa A. (International Multidisciplinary Research Journal, 2018)
Bacteria are carried in/on seeds by biofilm formation. However relatively few studies have been focused on the factors affecting biofilm formation ability of Xanthomonas axonopodis pv. vignicola (Xav) as a mechanism of transmission. Knowing the factors that enabling plant-pathogenic bacteria to form biofilm as a means to move and establish on/in the hosts provides the necessary basis to set up appropriate management approach. The study was conducted to determine factors affecting biofilm formation as mechanisms of seed transmission of Xanthomonas axonopodis pv. vignicola by growing bacterial cells in maize, millet, sorghum, Ife brown, Sampea7 extracts and extracts of Ife brown + 0.5 g nutrient glucose agar (NGA) in a 96 microlitre wells. The seeds extract were prepared by soaking one hundred seeds each of Ife brown, Sampea7, millet, sorghum and maize in a 250 ml flask containing 100 ml SDW and for 20 h. Bacterial suspension adjusted to ca. 4.5 x 107 cfu/ml was suspended in each of the extracts and the media and filled twelve wells each of the treatment. These were incubated for 72 h, 96 h and 120 h. afterwards, the wells were emptied and the wells were stained with 1 % crystal violet (CV) solution in 33 % (V/V) acetic acid for approximately 20 minutes. Excess CV was washed with SDW. The bound CV to the wells were solubilized with 200 µl of 33 % acetic acid or acetone – ethanol and quantified spectrophotometrically using Well Reader (GF 3000 microplate Reader –Bran scientific and Instrument Company England). Specific Biofilm formations (SBF) was calculated. The experiment was replicated two times and repeated 3 times. There was statistical difference between the biofilm formation induced by the different extracts and NGA. All the seeds extract induces biofilm formation and the level of biofilm formation varies with time and the nutrient status of the media or medium.